FACTORS AFFECTING MEDICAL DOCTOR TURNOVER IN THE HOSPITAL: A SYSTEMATIC REVIEW - Habsari, Angesti Drea; Ilyas, Jaslis (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Among others, healthcare professional is one of the main drivers in the hospital. Medical doctor plays an important role in patient-centered care system in the hospital, leading health services to patients, cooperating with other healthcare professionals. Medical doctor shortage and high turnover in the hospital has become a problem in many countries. High turnover of medical doctor can lead to an inadequate supply of health services, thereby compromising people?s access to health care and endangering the quality of patient care and safety. The objective of this study is to get an overview of the factors that affect medical doctor turnover in the hospital.Methods: A systematic review of articles published between 2014 and 2019 that contain information from all relevant published articles were extracted and analyzed. Results: The literature search and screening process resulted in 9 (nine) studies. From the selected studies, overtime, job satisfaction, and work stress are among the things that affect the turnover of medical doctor in the hospital. Conclusions: Consequences of high medical doctor turnover in the hospital are including financial loss, low patient satisfaction, and poor organizational practices. Factors affecting medical doctor turnover in the hospital are long work hours, job satisfaction, work stress, workplace condition, and hospital management.